P-7 The atlas programme for schools: supporting children to navigate their way through bereavement. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Birch, Katherine; Bridge, Hannah
Abstract : By the age of 16, almost eight out 10 young people have experienced the death of a close friend or relative. The negative impact of unresolved childhood bereavement may reduce academic achievement, increase risk of offending behaviour, teenage pregnancy and developing mental health difficulties (Ribbens McCarthy with Jessop, 2005; Akerman & Statham, 2014). Bereaved young people may find it difficult to talk to anyone about their experiences. With children spending over six hours a day in school, schools are a key source of support, constancy and consistency when families experience the turbulence of bereavement. A common theme in the research literature is that there are a wide range of outcomes for children who have experienced a close bereavement. All children and families are unique and have different experiences of bereavement and grief, and responses to them. A qualitative study (Abdelnoor & Hollins, 2004) found that while some children took a 'restorative approach' to school life, preferring to deal with loss-related issues elsewhere, others described chaos and distress in school following the bereavement. It is essential therefore that staff working within schools are confident in supporting bereaved young people and understand how bereavement impacts at different stages of the lifecycle. This paper discusses the initial outcomes from the ATLAS programme, established in 2017 to help schools support pupils as they navigate their way through their experiences of bereavement. Atlas aims to: Raise awareness of the extent and effects of bereavement on young people Support schools in the Wolverhampton area to develop effective bereavement policy and practice Equip staff with the knowledge, skills and confidence to support bereaved children Support achievement of national policy ambitions, including Ambition 6 'Each Community Is Prepared To Help' Provide focused training for early career teachers. The paper also includes a critical discussion of the role of different stakeholders.